Nanocrystalline Cellulose and Polyvinyl Alcohol Coating Application to Cardboard Packaging Papers and Investigation of the Effects on Paper Properties - YENİDOĞAN, SEMİHA (KAUNAS UNIV TECH, 2020)
In the packaging sector of the printing industry, different coating applications are tried and investigated in order to increase the surface appearance and performance characteristics of paper and cardboard. The printability, water and ink absorption capacity, frictional resistance, light sensitivity of the visual graphical design that are going to be printed on the packaging papers are some of them. In this study, different types of cardboards that are used as a packaging material were chosen and coated with nanocrystalline cellulose (NCC)/PVA at different rates (%). In order to determine effective and economical usage conditions, the coating solutions, at three different concentrations as 3 wt.%, 5 wt. %, 7 wt.%, were prepared. The coating was applied on the test papers, which were at the same weights (350 g/m(2)) and had different surface properties as matte glossy, bright glossy, American Bristol. NCC/PVA existence on the coated paper surface was confirmed with Fourier Transform Infrared Spectroscopy (ATR-FTIR). The impact of the coating, which was prepared at different concentrations, on the packaging materials was studied with respect to thickness, stiffness, water absorbability, contact angle and surface tension.
Keywords: nanocrystalline; nanocellulose; NCC; packaging paper; PVA; coating; cardboard coating; MECHANICAL-PROPERTIES; COMPOSITES; WATER